The effect of good corporate governance (GCG) and company characteristics on the timeliness of financial reporting - Atik Djayanti; Zainal Abidin (Institute of Computer Science (IOCS), 2023)
The purpose of this study was to determine the effect of good corporate governance and company characteristics on the timeliness of reporting. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2019 period before the covid 19 pandemic and the 2020-2021 period after the Covid 19 pandemic. and processed with Microsoft Excel 2019 and SPSS software. Based on the results of the study, empirical facts were obtained in the form of: 1) Independent commissioners have a large influence on the company's timeliness in reporting its financial statements; 2) Audit committee meetings have no effect on the timeliness of financial reports; 3) The size of the company influences the timeliness of the company's financial reporting.